Dinamika Sengketa Internasional Wilayah Ashmore Reef Antara Indonesia Dengan Australia - Rani Pajrin; Muhammad Razaq Firdaus; Vinky Wahyu Anjas Prianggoro; Sheva Andika Ramajagandhi (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The Ashmore Reef territorial dispute between Indonesia and Australia has attracted international attention over the past few decades. This journal aims to investigate the dynamics of this dispute. This research uses an international legal analysis approach to explore the legal basis and latest developments in dispute resolution. In addition, through careful analysis, this Journal also reviews the possible political, economic and environmental impacts that may arise as a result of this dispute.